Mudanças climáticas e agricultura no Brasil: impactos econômicos regionais e por cultivo familiar e patronal - Tarik Marques do Prado Tanure (2020)
The phenomenon of climate change affects a variety of aspects, ranging from ecosystem/biological to socioeconomic, involves gradual transformations along an extensive time horizon, causes externalities and expands uncertainties. Agricultural productivity, although determined, to a large extent, by productive factors, is extremely sensitive to temperature and precipitation changes, and therefore vulnerable to the effects of the climatic phenomenon. This thesis analyzes the future impacts of climate change on agricultural productivity of crops linked to family farmers and regular farming in Brazil, and its potential economic effects. The hypothesis that guided the study is that climate change will affect agricultural productivity throughout the 21st century and given this new scenario, crops linked to family farming will be more vulnerable to these effects, both by the lower financial, technical and informational capacity to deal with its effects, and by the lower focus of planning policies and climate adaptation research, which tend to focus on agribusiness-linked crops. Moreover, given the heterogeneity of the Brazilian agriculture and the impacts of climate change on the territory, the need to verify these effects is required, differentiating the impacts on crops and the type of producer. In this sense, the impacts of climate change on the agricultural productivity of family and regular farmers was estimated, using the RCP 4.5 and RCP 8.5 scenarios of global warming projection of the Intergovernmental Panel on Climate Change (IPCC), produced by the National Institute of Spatial Research (INPE), for the periods of 2021/2050 and 2051/2080. The variations in agricultural productivity were used as input in the Computable General Equilibrium (CGE) model developed in this thesis to project the economic impacts resulting from productivity changes. The model called Agriculture Regional Model - AGRO-BR, presents regional configuration composed of the 27 Federation Units and 42 agricultural sectors, disaggregated into family and regular producers. The results obtained indicate that the agricultural productivity of family farmers is more sensitive to climate change. The cassava, corn and bean crops, typical of family farming, would be, on average, impacted by loss of productivity. The sugar cane and soybean plantations would be impacted by productivity gains in the main producing regions. In terms of economic impacts, the North and Northeast regions would be negatively affected, the Midwest and Southeast would suffer moderate impacts, while the South region would benefit mostly. Despite the projections for most of the Federation Units being negative, São Paulo, Paraná and Rio Grande do Sul would show economic growth, mitigating the negative impacts on the national GDP, which would present a small retraction in both scenarios. The results also indicate that the phenomenon could contribute to the increase of intra-regional disparities and to the deterioration of food security conditions in Brazil, since it would negatively affect the less developed regions and the relevant crops for family farmers.